Microstructure evolution and constitutive modelling of microsize structures - Liu, Lin. (2013)
Given the small dimensions to be replicated for micro components, knowledge into their microstructure evolution is crucial for dimensional and property control. Constitutive model is useful to predict the final shape of the sintered micro components. In this paper, the microstructure evolution of 316L stainless steel microsize structures of Φ60 µm that was fabricated by micro metal injection moulding was examined via SEM and XRD. A constitutive model is established to simulate densification of the microsize structures and the contribution of lattice diffusion (Nabarro-Herring creep) is considered. The predictive capability of the model is verified by comparing the theoretical calculations with the experimental results. The influences of boundary energy on modelling results are discussed. It is found that the modelling results agree reasonably well with the experimental results.